2012
DOI: 10.1002/jbm.b.32657
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of exudates of human platelet‐rich fibrin gel in biodegradable fibrin scaffolds for tissue engineering of cartilage

Abstract: The goal of this study was to assess the incorporation of exudates of human platelet-rich fibrin (hPRF) that is abundant in platelet cytokines and growth factors into biodegradable fibrin (FB) scaffolds as a regeneration matrix for promoting chondrocyte proliferation and re-differentiation. hPRF was obtained from human blood by centrifugation without an anticoagulant, and the exudate of hPRF was collected and mixed with bovine fibrinogen, and then thrombin was added to form the FB scaffold. Proliferation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 58 publications
1
33
1
1
Order By: Relevance
“…Akeda and colleagues [29] reported that 10% PRP treatment significantly increased proteoglycan and Col II synthesis compared to treatments with 10% PPP or 10% FBS, with the major profiles of proteoglycan and collagens being similar to those seen in cells cultured with FBS, indicating maintenance of a stable chondrocyte phenotype with PRP exposure. Similar effects were also noted in human osteoarthritic chondrocytes [30]. The supernatant from platelet-rich fibrin (PRF) up-regulated the mRNA expression of Col II and aggrecan and increased synthesis of glycosaminoglycan and proteoglycan by chondrocytes cultured either on the two-dimensional surface of fibrin scaffolds or in three-dimensional scaffolds compared to controls without addition of exudate.…”
Section: Effect Of Platelet-rich Plasma On Cellsmentioning
confidence: 61%
See 1 more Smart Citation
“…Akeda and colleagues [29] reported that 10% PRP treatment significantly increased proteoglycan and Col II synthesis compared to treatments with 10% PPP or 10% FBS, with the major profiles of proteoglycan and collagens being similar to those seen in cells cultured with FBS, indicating maintenance of a stable chondrocyte phenotype with PRP exposure. Similar effects were also noted in human osteoarthritic chondrocytes [30]. The supernatant from platelet-rich fibrin (PRF) up-regulated the mRNA expression of Col II and aggrecan and increased synthesis of glycosaminoglycan and proteoglycan by chondrocytes cultured either on the two-dimensional surface of fibrin scaffolds or in three-dimensional scaffolds compared to controls without addition of exudate.…”
Section: Effect Of Platelet-rich Plasma On Cellsmentioning
confidence: 61%
“…When adult porcine chondrocytes were cultured in alginate beads in the presence of 10% PRP releasate (PRPr), 10% platelet-poor plasma (PPP) releasate or 10% fetal bovine serum (FBS) for 72 hours, the increase in DNA content in the PRP group was significantly higher than that in the PPP group and that in the FBS group [29]. The stimulatory effect of PRP on chondrocyte proliferation was also observed after 4, 8 and 12 days of in vitro culture, in either a monolayer or three-dimensional environment [30]. Additional studies revealed a dose- and time-dependent enhancement of chondrocyte proliferation by PRPr, even during the 20 day monolayer culture [31,32].…”
Section: Effect Of Platelet-rich Plasma On Cellsmentioning
confidence: 99%
“…In fact, there are studies where fibrin and agarose scaffolds are used for cartilage regeneration. 29 Fibrin and FA hydrogels could also be used for the regeneration of damaged skin or as subcutaneous adipose tissue, even though the value of the viscoelastic moduli of skin tissues (G 0 2 MPa) or subcutaneous adipose tissue (G 0 104 Pa; G 00 103 Pa) are higher than the ones measured for FA. 20 Again, the viscoelastic moduli of FA hydrogels could probably be increased above the values reported in this work by increasing the agarose content.…”
Section: Effect Of Agarose Contentmentioning
confidence: 99%
“…It has been shown that the concentrations of growth factors, proteins and lipids in PRFr are higher than those in supernatant serum . In addition, the PRFr up‐regulated the mRNA expressions of type II collagen aggrecan and increased synthesis of glycosaminoglycan and proteoglycan in human OA chondrocytes . Therefore, we hypothesized that PRFr may serve as a mixture of growth factors and improve injury repair.…”
Section: Introductionmentioning
confidence: 98%
“…25 In addition, the PRFr up-regulated the mRNA expressions of type II collagen aggrecan and increased synthesis of glycosaminoglycan and proteoglycan in human OA chondrocytes. 26 Therefore, we hypothesized that PRFr may serve as a mixture of growth factors and improve injury repair. In this study, we investigated the therapeutic effects of PRFr in combination with MSCs for articular cartilage regeneration in a rabbit model.…”
Section: Introductionmentioning
confidence: 99%